Does E-Money Affect Inflation In Indonesia - Andres Dharma Nurhalim (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study aims to explain the effect of electronic money on inflation and how much influence it has on the Indonesian economy. In this study the authors used a quantitative approach. The variables used are inflation, electronic money, exchange rate, money supply (M1), and BI interest rate. Result: The previous money supply (LQMprev) and the interest rate (BI Rate) were the main factors affecting inflation. In this result, e-money and exchange rates are not the main components driving inflation. Based on SPPS processing using regression, e-money and exchange rates do not have a significant effect on inflation in Indonesia, but LQMprev has a significant effect on inflation. From the results of this study it is still too early to analyze the effect of e-money on inflation because it is still relatively new in Indonesia.